ANALISIS POSISI TUBUH, SUDUT DAN GAYA DALAM LEMPAR CAKRAM ATLET PENGPROV PASI ACEH - Musran Musran; Syahrianursaifi Syahrianursaifi; Yulinar Yulinar; Erizal Kurniawan (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Discus throwing is a throwing number that requires several body abilities, including biomechanics of motion, body position, angle of movement and the magnitude of the force that will affect the results of the throw. The importance of correct motion biomechanics in discus throwing is to achieve a feat. This study aims to analyze the range of motion of the body position, the angle of movement and the magnitude of the force in discus throwing in Acehnese PASI athletes. Review based on correct biomechanics and proper elevation angle. This type of research is descriptive analysis, namely analyzing and presenting data systematically. This study uses a total sampling of 5 PASI Aceh discus throwing athletes. The movement angle position data is obtained through solidworks software, the magnitude of the force using the axis accelerometer sensor and software logger pro. The data analysis technique uses descriptive analysis. The results showed: 1) Body position in discus throwing with an average value of 3.47 in the